2009
DOI: 10.1016/j.cell.2009.11.015
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis for mRNA Recognition and Cleavage by the Ribosome-Dependent Endonuclease RelE

Abstract: SummaryTranslational control is widely used to adjust gene expression levels. During the stringent response in bacteria, mRNA is degraded on the ribosome by the ribosome-dependent endonuclease, RelE. The molecular basis for recognition of the ribosome and mRNA by RelE and the mechanism of cleavage are unknown. Here, we present crystal structures of E. coli RelE in isolation (2.5 Å) and bound to programmed Thermus thermophilus 70S ribosomes before (3.3 Å) and after (3.6 Å) cleavage. RelE occupies the A site and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
349
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 197 publications
(369 citation statements)
references
References 45 publications
13
349
3
Order By: Relevance
“…On the other hand, these observations, of course, do not exclude that particular TA loci have been recruited to perform other functions, as recently proposed for the mqsRA locus of E. coli (47). The entirely different tertiary folds of the translational inhibitors encoded by type II TA loci, such as RelE, MazF, and HicA, indicate that they have independent evolutionary origins (7,15,(48)(49)(50)(51). Therefore, the common genetic organization, transcriptional regulation, and cellular targets (i.e., translation) of type II TA loci suggest that these gene families emerged by convergent evolution.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…On the other hand, these observations, of course, do not exclude that particular TA loci have been recruited to perform other functions, as recently proposed for the mqsRA locus of E. coli (47). The entirely different tertiary folds of the translational inhibitors encoded by type II TA loci, such as RelE, MazF, and HicA, indicate that they have independent evolutionary origins (7,15,(48)(49)(50)(51). Therefore, the common genetic organization, transcriptional regulation, and cellular targets (i.e., translation) of type II TA loci suggest that these gene families emerged by convergent evolution.…”
Section: Discussionmentioning
confidence: 86%
“…RelE of E. coli belongs to a well-described toxin superfamily with many homologs in both bacteria and archaea (13). RelE is a riboendonuclease that cleaves mRNA positioned at the ribosomal A site, between the second and third bases of the A-site codon (14,15). Therefore, ectopic production of RelE rapidly shuts down translation and halts cell growth (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ribosome-dependent toxins cleave mRNAs on the ribosome between the second and third nucleotides of the aminoacyl (A)-site codon (21)(22)(23). Although collectively Escherichia coli ribosome-dependent toxins target a diverse range of codons, each individual toxin appears to have a strong codon preference and cleaves at defined positions along the mRNA (24)(25)(26).…”
mentioning
confidence: 99%
“…A few years later the first two chromosome-encoded type II TA loci, homologues of pemIK (also called mazEF), were identified [23]. We discovered the relBE module of E. coli (figure 1a) and showed that relE encodes an efficient inhibitor of global cellular translation [28,31] that cleaves mRNA codons at the ribosomal A-site [25,26]. Over the years, we have developed relBE of E. coli into a paradigm model system, not least because relBE homologues are abundantly present in bacterial and archaeal chromosomes [17].…”
Section: Introductionmentioning
confidence: 99%